Corpus Anarchicum - Dabashi, H. author. aut Link
X, 235 p.
Keywords: Dabashi's newest book is a meditation on suicidal violence in the immediate context of its most recent political surge and a critical examination of the radical transformation of the human body, supported by close readings of cinematic and artistic evidence.